The eClassroom used as a Teacher's Training Laboratory to Measure the Impact of Group Facilitation on Attending, Participation, Interaction, and Involvement. - Mia Lobel; Randy Swedburg; Mike Neubauer (International Review of Research in Open and Distributed Learning, 2002)
This paper describes and quantifies the role of group facilitation in an experiential, real-time, online, university level credit course entitled eAHSC/230 Interpersonal Communications and Relations. A new and unique group interaction pattern called parallel communication, as well as classical elements of group interaction are described and quantified. New measures of online group facilitation attributes with analogous face-to-face (F2F) counterparts are presented. Specifically, the impact of effective group facilitation on Attentiveness, on Interaction, on Involvement, and on Participation is explored. The paper also examines the eClassrom’s potential effectiveness as a real time teaching and training laboratory which also functions as a process observation tool that collects and feeds back interaction data, providing teachers and trainers immediate and ongoing measures of facilitation effectiveness.